PENGARUH DIFERENSIASI PRODUK, DIGITAL MARKETING DAN KEBIJAKAN HARGA TERHADAP KEPUTUSAN WISATAWAN MENGINAP DI THE COMPASS ROSE UBUD - I Nengah Suweca; Luh Komang Candra Dewi; Sourtua Marbun Marbun (Universitas Mahendradatta Denpasar, 2024)
AbstractThe tourism industry is an important sector in national development. Bali is a province in Indonesia which is well known for having extraordinary tourism potential. Hotel is an accommodation facility that provides lodging facilities as well as food and beverage services which are commercial in nature and are growing rapidly. The beauty of the beaches in Bali can be an added value for the hotel itself and an attraction for tourists who will stay at that place. The purpose of this study is to analyze the effect of Product Differentiation, Digital Marketing and Pricing Policies on Tourist Decisions di The Compass Rose Ubud.The research location is The Compass Rose Ubud Bali. The method of determining the sample using the method purposive sampling. The sample of this research is consumers or customers who are aged 17 years and over as many as 110 respondents. The analysis technique used is multiple linear regression analysis.The results of the study show that product differentiation has a positive and significant effect on tourists' decisions at The Compass Rose Ubud. Digital marketing positive and significant effect on tourists' decisions The Compass Rose Ubud. Pricing policy has a positive and significant effect on tourist decisions. Product differentiation, digital marketing and price policy has a positive and significant effect on tourists' decisions The Compass Rose Ubud. Differentiation variables the product has the most dominant influence on tourists' decisions at The Compass Rose Ubud.